Collagen modified porous pHEMA–TiO2 composite hydrogels for tissue engineering - Li, Chao; Liu, S.; Zheng, Y.; Lou, Xia (Elsevier, 2013)
Poly(2-hydroxyethyl methacrylate) (pHEMA) hydrogels are well known for their applications as vision correction devices including contact lenses and intraocular lenses. Like most other synthetic hydrogels, pHEMA is bio-inert and lacks cell binding sites for extended applications as tissue regeneration scaffolds. Collagen has been extensively used to enhance the cellular activities of biomaterials. However, modification with collagen molecules is often limited to the surface of hydrogels [1]. In this work, we report the preparation of collagen modified porous pHEMA–TiO2 composite hydrogels through the formation of a semi-interpenetrating polymer network and the observation of significantly improved cell activities on the modified pHEMA hydrogels. pHEMA and pHEMA–TiO2 composite hydrogels were first produced using a reported method [2]. Collagen modification was carried out by crosslinking collagen molecules (10 mg/ml) in the presence of hydrated pHEMA and pHEMA–TiO2, using 0.25% glutaraldehyde. The resulting hydrogels contain interconnected pores. Fibrous networks of collagen were observed on the cross section of the modified hydrogels (Fig. 1a, b). FTIR and UV–vis spectra also demonstrated the presence of the collagen molecules in the modified hydrogel matrices (data not shown). All hydrogels were well tolerated by 3T3 mouse fibroblast cells. The growth of both 3T3 fibroblast and hMSCs was significantly enhanced and accelerated only after incorporation of the collagen into the hydrogel matrices (Fig. 1c–f). Migration and in-growth of hMSCs into the collagen bonded hydrogel scaffolds were also well demonstrated in the laser confocal images which is of significant importance for the application of any scaffolding material in the regeneration of tissues.